A Novel Approach for Adsorption of Copper(II) Ions from Wastewater Using Cane Papyrus - Al-atabi, Mohammed jaafar (International Journal of Integrated Engineering, 2018)
Abstract:                 This study tested the suitability of  Cane Papyrus as a  biological sorbent  for the  removal of  copper ions (Cu2+) from  industrial  wastewater. Bath mode was  used and the effects  of the  following parameters  were investigated: adsorbent dosage (10 to 50 g/L), pH value (2 to 8.0). The Cane Papyrus were  characterized  by Fourier  transform infrared spectroscopy (FTIR)   Cu2+ions adsorption. The results revealed a higher efficiency of powdered adsorbents for Cu2+ removal. The highest adsorption efficiency was found to occur at pH 6 with 50 g/L Cane Papyrus for an experimental duration of 2 hours. These  derivatives  are  probably responsible  for  Cu2+  chemical  adsorption. The Freundlich isotherm model more suitably described the adsorption process than the langmuir model with linearized coefficients of 0.95 and 0.844 respectively. Pseudo-second order kinetic equation best described the kinetics of the reaction. Fourier transform infra-red analysis confirmed the presence of amino (–NH), carbonyl (–C=O) and hydroxyl (–OH) functional groups. Furthermore, 0.5M HCl was a better desorbing agent than 0.5 M NaOH and de-ionized water. The experimental data obtained demonstrated that Cane Papyrus  can be used as a suitable adsorbent for Copper(II) ion removal from wastewater.